Red Belts - Pendexter, Hugh, 1875-1940; Coleman, Ralph P. (Ralph Pallen), 1892-1968 (Salt Lake City, UT : Project Gutenberg, 2015)
"Red Belts" by Hugh Pendexter is a historical novel written in the early 20th century. Set in the tumultuous context of post-Revolutionary America, the book takes place in the aftermath of the American war for independence, focusing on the tensions between settlers and Native American tribes in the newly claimed territories. The narrative revolves around the struggles of characters such as Kirk Jackson, a ranger with ambitions tied to his love for Elsie Tonpit, while highlighting the broader conflict involving political intrigue, ambition, and the threat of war. The opening of "Red Belts" introduces readers to the rugged frontier town of Jonesboro, North Carolina, in 1784, where settlers are grappling with local lawlessness and external threats. It sets the stage for interpersonal conflicts, notably between Lon Hester, a drunken bully, and Polcher, a tavern-keeper with shadowy connections. The narrative builds tension as Hester$1 (Bs reckless behavior stirs unease among the townsfolk and hints at deeper conspiracies involving Major John Tonpit, a key figure in the community whose ambitions may align with Spanish interests. Amid this backdrop, the introduction of Kirk Jackson and his burgeoning relationship with Elsie hints at personal stakes intertwined with the unfolding political drama, establishing a story rich in both individual aspirations and collective struggles. (This is an automatically generated summary.)s
Release date is 2015-02-09
E-text prepared by Denis Pronovost, Shaun Pinder, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Frontier and pioneer life -- Tennessee -- Fiction